2018
DOI: 10.1021/acs.inorgchem.8b00573
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, and Optical Properties of Layered Perovskite Scandium Oxychlorides: Sr2ScO3Cl, Sr3Sc2O5Cl2, and Ba3Sc2O5Cl2

Abstract: We report the successful synthesis of three new Ruddlesden-Popper-type scandium oxychloride perovskites, SrScOCl, SrScOCl, and BaScOCl, by conventional solid-state reaction. Small single crystals of SrScOCl were obtained by a self-flux method, and the crystal structure was determined to belong to the tetragonal P4/ nmm space group ( a = 4.08066(14) Å, c = 14.1115(8) Å) by X-ray diffraction analysis. The scandium center forms a ScOCl octahedron with ordered apical oxygen and chlorine anions. The scandium cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…For example, for a lot of the oxychlorides, the metalchloride bond lengths are often above 3Å;, which is much longer than the expected covalent bond length of 2.4Å; or below. Other researchers who have studied these compounds have taken contrasting views on how to view the B -X bonding; some have rationalized the compounds as LPD's with severely distorted metal-O/X octahedra, (121,55) while other have regarded them as B O5 square pyramids with counter X anions. (122,123,124) Specific to the oxyhalide field, previous research did not always take advantage of DFT calculations to support the structural characterization, but one recent work on a set of new scandium oxychlorides found that the metal halide association was essentially nonbonding, and the B cation environment is best described as square pyramidal.…”
Section: Halide Ldpsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for a lot of the oxychlorides, the metalchloride bond lengths are often above 3Å;, which is much longer than the expected covalent bond length of 2.4Å; or below. Other researchers who have studied these compounds have taken contrasting views on how to view the B -X bonding; some have rationalized the compounds as LPD's with severely distorted metal-O/X octahedra, (121,55) while other have regarded them as B O5 square pyramids with counter X anions. (122,123,124) Specific to the oxyhalide field, previous research did not always take advantage of DFT calculations to support the structural characterization, but one recent work on a set of new scandium oxychlorides found that the metal halide association was essentially nonbonding, and the B cation environment is best described as square pyramidal.…”
Section: Halide Ldpsmentioning
confidence: 99%
“…(122,123,124) Specific to the oxyhalide field, previous research did not always take advantage of DFT calculations to support the structural characterization, but one recent work on a set of new scandium oxychlorides found that the metal halide association was essentially nonbonding, and the B cation environment is best described as square pyramidal. (125) There are, however, examples such as CsCaNb2O6F, (126) where the B -site metal-fluoride interaction is clearly bonding (bond length of 2.34Å). In general though, a defining feature of these anion ordered LDP structure type appears to be that they are strangely effective at inducing square pyramidal geometry in metals, even for those that are not known to commonly do so (Sc and In, in particular).…”
Section: Halide Ldpsmentioning
confidence: 99%
“…The crystal parameters of Ba 3 Y 2 O 5 Cl 2 , Sr 3 Sc 2 O 5 Cl 2 , and Sr 2 ScO 3 Cl were refined by the Rietveld method using the Z-code program . The crystal structures of Ba 3 Y 2 O 5 Cl 2 , Sr 3 Sc 2 O 5 Cl 2 , and Sr 2 ScO 3 Cl were refined using the crystal parameters in the literature , as initial parameters. X-ray fluorescence (XRF) spectra indicated the atomic ratios of Ba/Y/Cl = 3:2:2 for Ba 3 Y 2 O 5 Cl 2 , Sr/Sc/Cl = 3:2:2 for Sr 3 Sc 2 O 5 Cl 2 , and Sr/Sc/Cl = 2:1:1 for Sr 2 ScO 3 Cl, which agrees with the ideal ratios of Ba 3 Y 2 O 5 Cl 2 , Sr 3 Sc 2 O 5 Cl 2 , and Sr 2 ScO 3 Cl, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The bond-valence-based energy (BVE) of a test oxide ion (O 2– ) in the crystal structures of Ba 3 Y 2 O 5 Cl 2 , Sr 3 Sc 2 O 5 Cl 2 , and Sr 2 ScO 3 Cl was obtained with the SoftBV program to study the oxide-ion migration paths. The BVE landscapes were calculated with a spatial resolution of approximately 0.1 Å using the crystal structures reported in our previous works. , The crystal structures and BVE landscapes were drawn with VESTA …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation